Modelling of single spark interactions during electrical discharge coating - Algodi, Samer J.; Clare, Adam T.; Brown, Paul D. (Elsevier, 2018)
Electrical discharge coating (EDC) methods may be used to enhance the surface functionality of electrical discharge machined components. However, industrial uptake of EDC has been restricted due to limited understanding of the fundamental interactions between energy source and workpiece material. The fraction of energy transferred to the workpiece, Fv, as a consequence of sparking, is an important parameter which affects directly crater geometry and the microstructural development of the near surface modified layer. In this paper, a 2D transient heat transfer model is presented using finite difference methods, validated against experimental observations, to estimate effective values for Fv as a function of processing conditions. Through this method we can predict coating layer thicknesses and microstructures through appropriate consideration of heat flow into the system. Estimates for crater depths compared well with experimentally determined values for coating layer thicknesses, which increased with the increasing fraction of energy transfer to the workpiece. Predictions for heat transfer and cooling of melt pools, arising from single spark events, compared well with experimental observations for the developed cermet microstructures. In particular, intermediate processing conditions were associated with the development of complex, banded, fine-grained microstructures, reflecting differences in localised cooling rates and the competing pathways for heat conduction into the substrate and convection within the dielectric fluid. Increased pulse-on times were associated with a propensity towards increasing grain size and columnar growth, reflecting the higher energies imparted into the coatings and slower cooling rates.